Case report: COVID-19-associated mucormycosis co-infection with Lomentospora prolificans: The first case and review on multiple fungal co-infections during COVID-19 pandemic - Erami, Mahzad; Mirhendi, Hossein; Momen-Heravi, Mansooreh; Sharif, Alireza; Hashemi Hezaveh, Seyed Jamal; Matini, Amir Hassan; Ahsaniarani, Amir Hossein; Aboutalebian, Shima (Frontiers in Medicine, 2023)
Along with the pandemic COVID-19 spreads, new clinical challenges have emerged in the health care settings, among which there is a high risk of secondary invasive fungal infections with significant mortality. Here, we report a case of invasive fungal rhino orbital sinusitis due to the simultaneous co-infection by Rhizopus oryzae and Lomentospora prolificans, both identified by sequencing, in a 70-year-old Afghanistanian female with COVID-19. The patient was subjected to surgical debridement as well as taking liposomal amphotericin B, voriconazole, and on discharge, her condition was good. As far as we know, this is the first case of co-infection of COVID-19-associated mucormycosis (CAM) and Lomentospora prolificans infection. Multiple fungal co-infections in COVID-19 patients are reviewed.